How Leadership in a Hospital can Improve Health Services in a Private Hospital in Yogyakarta - Salem Salah (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2019)
Background:Leadership is a pivotal issue that influences the successfulness and failure of any health organizations as an integral part of national development which aims to increase awareness. Objective: To analyze the effects of how leadership can improve the health services, Methods: The study was a qualitative research, the data gathering was conducted through interview with staff, director and manager in the private hospital of Yogyakarta. Results: Good leadership can improve health and quality services depending on the skill as well as the style of leadership transformation, in which it can improve the hospital in order to give the best services and facilities.Conclusion: Leadership depends on a personality that expands the position of a leader. Any effective leadership skills should be possessed by every leader, involving responsibility, developing strategies to organize resources and empowering staff to develop the organization specialization in hospital for improving health services in a private hospital in Yogyakarta.